Best Answer

To solve the simultaneous equations:

- x + y = 6
- -x + 3y = -2

Add the two equations together to get:

(x + -x) + (y + 3y) = (6 + -2)

â‡’ 0 + 4y = 4

â‡’ 4y = 4

â‡’ y = 1 (dividing both sides by 4)

Substitute this value for y in the first equation to get:

x + 1 = 6

â‡’ x = 5 (subtracting 1 from both sides)

Substitute for x and y found in the second equation to check:

-x + 3y = -(5) + 3(1)

= -5 + 3

= -2 as required

Answer: x = 5, y = 1

Or (in coordinate form) the point (5, 1) is where the lines x + y = 6 and -x + 3y = -2 meet.

Q: How do you solve x plus y equals 6 and -x plus 3y equals -2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x+3y=2 x= -5 y = 1

x = 5, y = -1

10 - (3y + 2) = 2 First solve the bracket: 10 - 3y + 2 = 2 Bring all constants to one side: 10 + 2 - 2 = 3y Simplify: 10 = 3y y = 31/3 (3.33333333333)

7y = 3y - 12 4y = -12 y = -3

x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5

Related questions

x+3y=2 x= -5 y = 1

x = 5, y = -1

10 - (3y + 2) = 2 First solve the bracket: 10 - 3y + 2 = 2 Bring all constants to one side: 10 + 2 - 2 = 3y Simplify: 10 = 3y y = 31/3 (3.33333333333)

7y = 3y - 12 4y = -12 y = -3

x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5

To solve for 2 unknown variables you need 2 independent equations. You have only 1.

Multiply first equation by 1.5, giving 3x + 3y = 12, but we are told that 3x + 3y = 6. If there isn't an error in the question then 2 = 1!

2 - (y + 2) = 3y Remove brackets: 2 - y - 2 = 3y Combine like terms: 0 = 4y Divide both sides by 4: 0 = y

If: y-2+3y =10 Then: y+3y = 10+2 And: 4y = 12 Divide both sides by 4 to find the value of y: y = 3

2x + 3y = 12 x = 1.45, so 2 * 1.45 + 3y = 12 2.9 + 3y = 12 3y = 12 - 2.9 = 9.1 y = 9.1/3 = 3.0333... or 91/30 or 3 1/30.

2x + 3y = 11Subract 2x from each side:3y = 11 - 2xDivide both sides by 3:y = 11/3 - (2/3)x

(2,3)